(untitled) (Singapore, 2017)
This book still recognizes the synergy between communication and culture and how that interface influences human interactions. More specifically, it is about what happens when people of different cultures engage in communication with the objective of sharing ideas, information, and perspectives.
Keywords: Giao tiếp và văn hóa,Communication and culture